2022
DOI: 10.1096/fj.202200398rr
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term aerobic conditioning prior to resistance training augments muscle hypertrophy and satellite cell content in healthy young men and women

Abstract: Factors influencing inter-individual variability of responses to resistance training(RT) remain to be fully elucidated. We have proposed the importance of capillarization in skeletal muscle for the satellite cell (SC) response to RT-induced muscle hypertrophy, and hypothesized that aerobic conditioning (AC) would augment RT-induced adaptations. Fourteen healthy young (22 ± 2 years) men and women underwent AC via 6 weeks of unilateral cycling followed by 10 weeks of bilateral RT to investigate how AC alters SC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 50 publications
(127 reference statements)
1
13
2
Order By: Relevance
“…Work in middle-aged women has also demonstrated that endurance training is able to alter the acute SC response to a bout of resistance exercise ( 39 ). The participants in the present study experienced an increase in V̇ o 2 peak and skeletal muscle capillarization following single-legged AC ( 28 ), which was associated with an augmented type-I SC content, further supporting the notion that training status and specifically capillary content can impact SC function.…”
Section: Discussion/conclusionsupporting
confidence: 79%
See 3 more Smart Citations
“…Work in middle-aged women has also demonstrated that endurance training is able to alter the acute SC response to a bout of resistance exercise ( 39 ). The participants in the present study experienced an increase in V̇ o 2 peak and skeletal muscle capillarization following single-legged AC ( 28 ), which was associated with an augmented type-I SC content, further supporting the notion that training status and specifically capillary content can impact SC function.…”
Section: Discussion/conclusionsupporting
confidence: 79%
“…Another study in sedentary middle-aged individuals that completed 12 wk of aerobic conditioning also reported an increase in type-I SC content, however, this was also accompanied by an increase in type-I fiber CSA ( 42 ). Although the participants in our study did not increase type-I CSA following aerobic conditioning ( 28 ), previous work by our laboratory has demonstrated an increase in activated SC following aerobic conditioning, which may act as an anticipatory response for future stimuli ( 34 ).…”
Section: Discussion/conclusioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In addition, while several studies have investigated the effects of concurrent training, when both RT and ET are combined within the same training session or program, no study to date has employed a design that investigated RTonly followed by ET-only. This is especially relevant considering a recent study reported that prior ET facilitated adaptations to a subsequent period of RT (16).…”
Section: Abstract: Aerobic Training Strength Training Hiit Mitochondr...mentioning
confidence: 92%